FARMERS’ PROBLEMS IN THE ERA PANDEMIC COVID-19 - Musviro; Anggia Astuti; Primasari Mahardhika Rahmawati; Suhari (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2022)
Background: During the Covid-19 pandemic there was a high risk of emergencies and disasters in agricultural areas. So that there are many problems for farmers in rural areas who generally have minimal information when compared to urban areas, especially in terms of accessing health information about Covid-19, this will certainly have an impact on different mindsets and perceptions in dealing with which pandemic. The Covid-19 pandemic is something new for the community. Efforts to deal with farmers' problems in the Covid-19 pandemic era by preventing the risk of emergencies and disasters in agricultural and livestock areas. Objectives: This study aimed to dig deeper into the problems of farmers in the Covid-19 era. Methods: The design of this study used an interpretive qualitative approach carried out through the Focus Group Discussion (FGD) method involving 10 farmer respondents. Data were collected using a thematic analysis approach based on Krueger, R and Casey, M. Results: The results of the interviews resulted in five major themes, namely the theme of self-protection tools as a covid-19 shield, Knowledge as a millennial farmer, supporting facilities for obtaining information, working environment conditions, marketing farm produce, change in work behavior. Conclusion: The problems of farmers in the Covid-19 area tend to see problems in terms of health but also have an impact on agricultural output, work behavior so that it needs attention to overcome problems to deal with farmers' problems during the Covid-19 pandemic.